2000
DOI: 10.1530/eje.0.1420269
|View full text |Cite
|
Sign up to set email alerts
|

Allopregnanolone concentrations and premenstrual syndrome

Abstract: Objective: To evaluate basal allopregnanolone and progesterone in both phases of the menstrual cycle in women suffering from premenstrual syndrome (PMS) and their response to a GnRH test. Design: We selected 56 women (28 patients with PMS and 28 controls) aged between 18 and 32 years. Blood samples were drawn in both follicular and phases. Twenty-eight women (14 patients with PMS and 14 controls) underwent a GnRH test in the luteal phase. Methods: We evaluated allopregnanolone by RIA, using a specific antibody… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
83
1
1

Year Published

2002
2002
2012
2012

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 173 publications
(88 citation statements)
references
References 19 publications
3
83
1
1
Order By: Relevance
“…It is also consistent with the endocrine challenge work of Monteleone et al (2000) and Lombardi et al (2004) in PMDD women. Despite the fact that those investigators reported lower, and not higher, baseline allopregnanolone in PMDD (Table 1), in response to an ACTH stimulation test following dexamethasone suppression, PMDD women had a significantly blunted adrenal allopregnanolone response compared with controls during the luteal phase (see Fig.…”
Section: Allopregnanolone Responses To Stress In Pmddsupporting
confidence: 87%
See 3 more Smart Citations
“…It is also consistent with the endocrine challenge work of Monteleone et al (2000) and Lombardi et al (2004) in PMDD women. Despite the fact that those investigators reported lower, and not higher, baseline allopregnanolone in PMDD (Table 1), in response to an ACTH stimulation test following dexamethasone suppression, PMDD women had a significantly blunted adrenal allopregnanolone response compared with controls during the luteal phase (see Fig.…”
Section: Allopregnanolone Responses To Stress In Pmddsupporting
confidence: 87%
“…Thus, these data suggest that histories of depression may be associated with persistent, long-term effects on allopregnanolone responsivity to stress and that the greater likelihood of prior depression in PMDD women may have contributed to previous findings for lower allopregnanolone concentrations or blunted allopregnanolone responsivity to challenge in PMDD women (Rapkin et al, 1997;Monteleone et al, 2000;Girdler et al, 2001;Lombardi et al, 2004). Moreover, to the extent that allopregnanolone negatively modulates the HPA axis following stress, then our results are also consistent with HPA axis abnormalities seen in depression, since it is well established that a large proportion of patients with melancholy depression are hypercortisolimic (Nemeroff, 1998) and show exaggerated HPA axis responses to mental stress (Heim et al, 2000;Young and Breslau, 2004).…”
Section: Histories Of Depression and Allopregnanolone Stress Responsimentioning
confidence: 69%
See 2 more Smart Citations
“…Although estrogen and progesterone have been shown in some studies to enhance and diminish HPA axis activation (Fonseca et al, 2001;Patchev et al, 1994), respectively, ALLO concentrations in plasma and brain increase as a result of stress (Barbaccia et al, 1997(Barbaccia et al, , 2001), perhaps as a compensatory mechanism. Women with PMDD fail to demonstrate the normal increase in ALLO seen in healthy subjects under conditions of stress (Monteleone et al, 2000;Girdler et al, 2001;Droogleever Fortuyn et al, 2004;Lombardi et al, 2004), or during HPA axis activation with ACTH administration (Genazzani et al, 1998;Lombardi et al, 2004). In the context of this study, the acoustic startle procedure can be viewed as mildly stress inducing.…”
Section: Discussionmentioning
confidence: 94%